THE RELATIONSHIP BETWEEN INTERNET ADDICTION AND IMPULSIVE BUYING AMONG STUDENTS OF SMA NEGERI 1 SALATIGA WHO USE E-COMMERCE - Dani Aji Kartiko; Dewita Karema Sarajar (RADJA PUBLIKA, 2026)
The development of the internet and technology cannot be separated from human life in this modern era. This condition is experienced by all groups, particularly senior high school students who are entering adolescence and tend to have unstable emotions. This study was conducted to analyze the relationship between internet addiction and impulsive buying. The participants of this study consisted of 209 respondents who were students of SMA Negeri 1 Salatiga from grades 10 to 12 and users of e-commerce, selected using a purposive sampling method. The measurements were conducted using the Impulsive Buying Tendency Scale (IBTS) and the Internet Addiction Test (IAT). Data analysis was carried out using Pearson correlation analysis, which indicated a positive and significant relationship between internet addiction and impulsive buying, with a correlation coefficient of r = 0.207 and a significance value of p = 0.003 (p < 0.05). These results indicate that the higher the level of internet addiction experienced by students, the higher their tendency to engage in impulsive buying behavior. The findings of this study suggest that internet addiction is one of the factors associated with impulsive buying among students of SMA Negeri 1 Salatiga, particularly those who use e-commerce.